Lithium secondary battery

By adopting an electrodeless structure and appropriately adjusting the electrolyte volume ratio in large-capacity cylindrical lithium secondary batteries, the heating and safety problems of traditional batteries in large-capacity situations are solved, and better output and life characteristics are achieved.

CN119366029APending Publication Date: 2025-01-24LG ENERGY SOLUTION LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202380045224.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-12-21
Filing Date
2023-12-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Traditional cylindrical lithium secondary batteries have a high capacity concentration, resulting in high heat generation, poor current collection efficiency, and there is a risk of fire or explosion during fast charging.

Method used

A lithium secondary battery design using a tabless structure, in which the uncoated parts of the positive plate and the negative plate serve as electrode tabs without forming separate electrode tabs, and the volume ratio of the electrolyte is adjusted to occupy the positive plate, The total pore volume of the negative electrode plate and the separator is not less than 101% by volume and not more than 119% by volume.

Benefits of technology

Effectively reduce the heat inside the battery, improve the heat safety, and ensure that the electrolyte is fully impregnated into the electrode component, thereby improving the output characteristics and life characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119366029A_ABST
    Figure CN119366029A_ABST
Patent Text Reader

Abstract

The present invention provides a lithium secondary battery comprising: an electrode assembly in which a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate are wound in one direction; a battery can accommodating the electrode assembly; an electrolyte injected into the battery can; and a sealing body sealing the open end of the battery can, in which the positive plate and the negative plate each comprise an uncoated portion in which an active material layer is not formed, and at least a portion of the uncoated portion of the positive plate or the negative plate defines an electrode tab, in which the active material layer is formed on the basis of the total pore volume of the positive plate, the negative plate, and the separator. The volume occupied by the electrolyte is from 101% by volume to 119% by volume (inclusive).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to Korean Patent Application No. 10-2022-0183661, filed on December 23, 2022, and Korean Patent Application No. 10-2022-0183669, filed on December 23, 2022, the disclosures of which are incorporated herein by reference in their entirety. Technical Field

[0003] The invention relates to a lithium secondary battery. Background Art

[0004] With the development of technologies such as electric vehicles and portable electronic devices, the demand for lithium secondary batteries as energy sources is rapidly increasing.

[0005] Lithium secondary batteries can be divided into cylindrical, prismatic and pouch batteries according to the type of battery shell. Among them, the cylindrical battery has a form in which a jelly roll type electrode assembly is contained in a cylindrical battery can, and then the top of the battery can is covered with a cover plate for sealing, wherein the jelly roll type electrode assembly is made by stacking a sheet-like positive electrode plate, a separator and a negative electrode plate in sequence, and then winding them in one direction. The positive electrode plate and the negative electrode plate are respectively provided with a positive electrode ear and a negative electrode ear having a strip shape, wherein the positive electrode ear and the negative electrode ear are connected to the electrode terminal, thereby being electrically connected to an external power source. For reference, the positive terminal is the cover plate and the negative terminal is the battery can. However, in the case of a conventional cylindrical battery having such a structure, there is a problem that the current is concentrated on the strip electrode ear, resulting in high resistance, high heat generation and poor current collection efficiency.

[0006] At the same time, with the development of electric vehicle technology in recent years, the demand for large-capacity batteries has increased, so it is necessary to develop large-volume large cylindrical batteries. In the case of small cylindrical batteries commonly used in the prior art (i.e., cylindrical batteries with 1865 or 2170 form factors), due to the small capacity, resistance and heat generation do not significantly affect battery performance. However, if the specifications of conventional small cylindrical batteries are applied to large cylindrical batteries intact, serious problems may arise in terms of battery safety.

[0007] This is because when the battery size increases, the amount of heat and gas generated inside the battery also increases, and the temperature and pressure inside the battery will increase due to this heat and gas, which may cause the battery to catch fire or explode. In order to prevent this, the heat and gas inside the battery must be properly discharged to the outside. To this end, the cross-sectional area of ​​the battery, which serves as a channel for discharging heat to the outside of the battery, must increase as the volume increases. However, since the increase in cross-sectional area is usually not as large as the increase in volume, the heat generated inside the battery increases as the battery becomes larger, increasing the risk of explosion and reducing output. In addition, when fast charging is performed at high voltage, a large amount of heat may be generated in a short period of time around the electrode tabs, which may cause the battery to catch fire.

[0008] Therefore, by adopting a structure in which the uncoated portions of the positive and negative electrode plates are used as electrode tabs without forming separate electrode tabs (eg, a tab-free structure), the problem of current concentration around the electrode tabs can be solved.

[0009] However, if this tab-free structure is adopted, the layout and structure of the internal space are different from those of conventional cylindrical lithium secondary batteries, so its characteristics are also different from those of conventional cylindrical batteries. For example, in conventional cylindrical lithium secondary batteries, as the injection amount increases, the electrolyte can be fully impregnated into the electrode assembly, thereby improving the overall characteristics of the lithium secondary battery. However, in the case of a large-capacity lithium secondary battery without a tab structure, the internal structure, spatial layout and impregnation characteristics of the wound electrode assembly are different from those of conventional cylindrical lithium secondary batteries. Therefore, when the amount of injected electrolyte increases, there is a problem that the electrolyte impregnation is reduced due to the increase in the internal pressure of the electrode assembly. Summary of the invention

[0010] Technical issues

[0011] The present invention aims to solve the above-mentioned problems and has the object of providing a high-capacity lithium secondary battery having a tab-less structure with improved electrolyte impregnation and thus excellent overall performance such as output and life characteristics.

[0012] Technical Solution

[0013] According to one embodiment, the present invention provides a lithium secondary battery, comprising: an electrode assembly wound in one direction including a positive electrode plate, a negative electrode plate, and a separator inserted between the positive electrode plate and the negative electrode plate; a battery can accommodating the electrode assembly; an electrolyte injected into the battery can; and a sealant sealing the open end of the battery can, wherein the positive electrode plate and the negative electrode plate each include an uncoated portion in which an active material layer is not formed, and at least a portion of the uncoated portion of the positive electrode plate or the negative electrode plate defines an electrode tab, wherein the volume occupied by the electrolyte is greater than 101 volume % and less than 119 volume % based on the total pore volume of the positive electrode plate, the negative electrode plate, and the separator.

[0014] Beneficial Effects

[0015] The lithium secondary battery of the present invention may have a structure in which the uncoated portions of the positive plate and the negative plate are used as electrode tabs without forming separate electrode tabs (e.g., a tab-free structure). In conventional cylindrical batteries with electrode tabs, a large amount of current is concentrated on the electrode tabs during charging, so a large amount of heat is generated around the electrode tabs. Especially during fast charging, this phenomenon becomes serious, and there is a risk of battery fire or explosion. In comparison, the cylindrical lithium secondary battery with a tab-free structure of the present invention may have a structure in which an uncoated portion of an active material layer is not formed at the ends of the positive plate and the negative plate, and the uncoated portion is connected to the electrode terminal by welding it to a collector plate having a larger cross-sectional area. Compared with conventional batteries with electrode tabs, the current concentration in this tab-free battery is lower, so the heat inside the battery can be effectively reduced, and the thermal safety of the battery can be improved.

[0016] In addition, in the lithium secondary battery of the present invention, the volume occupied by the electrolyte is adjusted to be more than 101 volume % and less than 119 volume % of the total pore volume of the positive plate, the negative plate and the separator, so that even in a large-capacity cylindrical lithium secondary battery with a non-electrode structure, the electrolyte can be fully impregnated into the electrode assembly, thereby obtaining excellent output characteristics and life characteristics. In particular, the loss of available electrolyte is reduced, so that a large-capacity lithium secondary battery with excellent low-temperature life characteristics can be realized. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 1 is a cross-sectional view showing the structure of a cylindrical battery without a tab structure according to an embodiment of the present invention.

[0018] Figure 2 FIG. 1 is a cross-sectional view showing the structure of a cylindrical battery without a tab structure according to another embodiment of the present invention. DETAILED DESCRIPTION

[0019] Hereinafter, the present invention will be described in more detail.

[0020] The terms or words used in the specification and claims of this application should not be interpreted as limited to their ordinary meanings or dictionary meanings, but should be interpreted as meanings and concepts consistent with the technical spirit of the present invention based on the principle that the inventor can appropriately define the concepts of the terms in order to best explain his invention.

[0021] In this specification, "primary particles" refer to particle units that do not have a grain boundary in appearance when observed with a scanning electron microscope at a field of view of 5,000 to 20,000 times. "Average particle size of primary particles" refers to the arithmetic mean value calculated by measuring the particle size of primary particles observed in a scanning electron microscope image.

[0022] In the present invention, "secondary particles" refer to particles formed by agglomeration of multiple primary particles. In the present invention, secondary particles formed by agglomeration of 10 or less primary particles are referred to as quasi-single particles to distinguish them from conventional secondary particles formed by agglomeration of tens to hundreds of primary particles.

[0023] In the present invention, “D 50 ” refers to the particle size of 50% of the volume cumulative particle size distribution of the positive electrode active material powder, which can be measured using a laser diffraction method. For example, the positive electrode active material powder is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), and irradiated with an ultrasonic wave of about 28 kHz with an output power of 60 W. Thereafter, the average particle size can be determined by obtaining a volume cumulative particle size distribution graph and then obtaining a particle size corresponding to 50% of the volume cumulative amount.

[0024] Electrolytes

[0025] Based on the total pore volume of the positive plate, the negative plate and the separator, the electrolyte injection amount contained in the lithium secondary battery of the present invention may be 101 volume % or more and 119 volume % or less, preferably 101 volume % or more and 115 volume % or less, and most preferably 101 volume % or more and 108 volume % or less. In this case, the electrolyte can fully impregnate the electrode assembly, thereby obtaining excellent output characteristics and life characteristics. In particular, when the injection amount is less than the above range, the amount of electrolyte through which lithium ions can move is reduced, thereby deteriorating the output characteristics, and the loss of available electrolyte increases, thereby resulting in a high lithium precipitation rate at low temperatures, so that the low temperature life characteristics are poor. In addition, when the injection amount exceeds the above range, due to the increase in the amount of electrolyte, the internal pressure increases, and the impregnation of the electrolyte is reduced, resulting in deterioration of the output and life characteristics.

[0026] The viscosity of the electrolyte used in the lithium secondary battery of the present invention at 20°C may be 3.5 cP or more and 4.2 cP or less, preferably 3.55 cP or more and 4.15 cP or less. The viscosity can be measured with an Ostwald viscometer. When the viscosity meets the above range, the impregnation of the electrolyte becomes appropriate, and therefore, when the injection fraction range of the present invention is applied, optimal performance can be provided.

[0027] The electrolyte used in the lithium secondary battery of the present invention may include a lithium salt, an organic solvent, and an additive.

[0028] Lithium salts are used as electrolyte salts in lithium secondary batteries and as a medium for transporting ions. Generally, lithium salts may include, for example, Li + as a cation, and selected from the group consisting of F - , Cl - Br - ,I - 、NO3 - 、N(CN)2 - 、BF4 - 、ClO4 - , B 10 Cl 10 - 、AlCl4 - 、AlO2 - PF6 - CF3SO3 - 、CH3CO2 - CF3CO2 - 、AsF6 - 、SbF6 - 、CH3SO3 - 、(CF3CF2SO2)2N - 、(CF3SO2)2N - 、(FSO2)2N - 、BF2C2O4 - , BC4O8 - PF4C2O4 - PF2C4O8 - 、(CF3)2PF4 - 、(CF3)3PF3 - 、(CF3)4PF2 - 、(CF3)5PF - 、(CF3)6P - 、C4F9SO3 - CF3CF2SO3 - CF3CF2(CF3)2CO - 、(CF3SO2)2CH - CF3(CF2)7SO3 - and SCN - At least one of the group consisting of is used as an anion.

[0029] Specifically, the lithium salt may include a salt selected from the group consisting of LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10, LiAlCl4, LiAlO2, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiN(SO2F)2 (lithium bis(fluorosulfonyl)imide; LiFSI), LiN(SO2CF2CF3)2 (lithium bis(perfluoroethanesulfonyl)imide; LiBETI) and LiN(SO2CF3)2 (lithium bis(trifluoromethanesulfonyl)imide; LiTFSI) any one or a mixture of two or more of the group consisting of. In addition, any lithium salt commonly used in the electrolyte of a lithium secondary battery can be used without limitation.

[0030] The concentration of the lithium salt contained in the electrolyte may be 1.0 M to 1.5 M, preferably 1.1 M to 1.3 M, to achieve optimal electrolyte impregnation for large-capacity cylindrical lithium secondary batteries. When the concentration of the lithium salt satisfies the above range, the effect of improving the cycle characteristics when the lithium secondary battery is stored at high temperature is sufficient, and the viscosity of the nonaqueous electrolyte may be appropriate, thereby improving the electrolyte impregnation.

[0031] The organic solvent may include at least one organic solvent selected from the group consisting of a cyclic carbonate-based organic solvent, a linear carbonate-based organic solvent, a linear ester-based organic solvent, and a cyclic ester-based organic solvent.

[0032] Specifically, the organic solvent may include a cyclic carbonate-based organic solvent, a linear carbonate-based organic solvent, and a mixed organic solvent thereof.

[0033] The cyclic carbonate organic solvent is a high-viscosity organic solvent with a high dielectric constant, and therefore can easily dissociate the lithium salt in the electrolyte. As a specific example, it can include at least one organic solvent selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate and vinylene carbonate, and in particular can include ethylene carbonate.

[0034] Based on the total volume of the organic solvent, the content of cyclic carbonate, such as ethylene carbonate, can be 15 volume % to 30 volume %, preferably 15 volume % to 25 volume %, and most preferably 15 volume % to 20 volume %. When the content of ethylene carbonate is within the above range, an optimized electrolyte can be provided in terms of viscosity and performance.

[0035] In addition, the straight-chain carbonate organic solvent is an organic solvent with low viscosity and low dielectric constant, and as a representative example, it can include at least one organic solvent selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate and ethyl propyl carbonate, specifically ethyl methyl carbonate (EMC).

[0036] Based on the total volume of the organic solvent, the content of the linear carbonate, for example ethyl methyl carbonate, can be 15 volume % to 30 volume %, preferably 15 volume % to 25 volume %, and most preferably 15 volume % to 20 volume %. When the content of ethyl methyl carbonate is within the above range, an optimized electrolyte can be provided in terms of viscosity and performance.

[0037] The organic solvent contained in the electrolyte of the present invention preferably contains ethylene carbonate (EC) and ethyl methyl carbonate (EMC), and the content of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) is less than 25 volume % of the total volume of the organic solvent. In this case, since the impregnation of the electrolyte becomes suitable, the electrolyte can be fully impregnated into the electrode assembly when the injection fraction range of the present invention is applied. Therefore, the lithium secondary battery of the present invention can achieve excellent results in terms of output characteristics and life characteristics.

[0038] The organic solvent may include ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of about 1:0.25 to about 1:1.15, preferably about 1:0.2 to about 1:1.1.

[0039] The organic solvent may further include dimethyl carbonate (DMC).

[0040] In addition, in order to manufacture an electrolyte with high ionic conductivity, in addition to at least one carbonate organic solvent selected from the group consisting of cyclic carbonate organic solvents and linear carbonate organic solvents, the organic solvent may further contain at least one ester organic solvent selected from the group consisting of linear ester organic solvents and cyclic ester organic solvents.

[0041] Specific examples of such a linear ester organic solvent may include at least one organic solvent selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate.

[0042] In addition, the cyclic ester organic solvent may include at least one organic solvent selected from the group consisting of γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone.

[0043] Meanwhile, if necessary, the organic solvent may be added to an organic solvent commonly used in a non-aqueous electrolyte without limitation, for example, at least one organic solvent selected from ether organic solvents, glycol ether organic solvents and nitrile organic solvents may be further included.

[0044] The ether solvent may be any one selected from the group consisting of dimethyl ether, ethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, 1,3-dioxolane (DOL) and 2,2-bis(trifluoromethyl)-1,3-dioxolane (TFDOL), or a mixture of two or more thereof, but is not limited thereto.

[0045] The glycol ether solvent is a solvent having a higher dielectric constant and a lower surface tension and a lower reactivity with metals than straight-chain carbonate organic solvents, and may include at least one selected from the group consisting of dimethoxyethane (glyme dimethyl ether, DME), diethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether (TEGDME), but is not limited thereto.

[0046] The nitrile solvent may be at least one selected from the group consisting of acetonitrile, propionitrile, butyronitrile, valeronitrile, octanonitrile, heptanecarbonitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, benzyl cyanide, 2-fluorophenyl cyanide and 4-fluorophenyl cyanide, but is not limited thereto.

[0047] The non-aqueous electrolyte of the present invention may contain electrolyte additives to prevent the non-aqueous electrolyte from decomposing in a high power environment and causing negative electrode collapse, or to further improve low-temperature high-rate discharge characteristics, high-temperature stability, prevent overcharging, and inhibit battery expansion at high temperatures.

[0048] As a representative example, the electrolyte additive may include at least one SEI film-forming additive selected from the group consisting of cyclic carbonate compounds, halogenated carbonate compounds, sultone compounds, sulfate ester / salt compounds, phosphate ester / salt compounds, borate ester / salt compounds, nitrile compounds, benzene compounds, amine compounds, silane compounds and lithium salt compounds.

[0049] The cyclic carbonate compound may be vinylene carbonate (VC) or vinyl ethylene carbonate.

[0050] The cyclic carbonate-based compound may be included in an amount of 0.1 wt % to 3 wt %, preferably 1 wt % to 3 wt %, and most preferably 1.5 wt % to 2.5 wt %, based on the total weight of the electrolyte.

[0051] The halogenated carbonate compound may be fluoroethylene carbonate (FEC).

[0052] The sultone compound may be at least one compound selected from the group consisting of 1,3-propane sultone (PS), 1,4-butane sultone, ethane sultone, 1,3-propene sultone (PRS), 1,4-butene sultone, and 1-methyl-1,3-propene sultone.

[0053] The sultone compound may be included in an amount of 0.1 wt % to 2 wt %, preferably 0.1 wt % to 1.5 wt %, and most preferably 0.8 wt % to 1.2 wt %, based on the total weight of the electrolyte.

[0054] The sulfate compound may be ethylene sulfate (Esa), trimethylene sulfate (TMS) or methyl trimethylene sulfate (MTMS).

[0055] The phosphate compound may be at least one compound selected from the group consisting of lithium difluorobisoxalate phosphate, lithium difluorophosphate, tris(trimethylsilyl) phosphate, tris(trimethylsilyl) phosphite, tris(2,2,2-trifluoroethyl) phosphate and tris(2,2,2-trifluoroethyl) phosphite compounds.

[0056] The borate ester / salt compound may be tetraphenylborate, lithium difluoroborate oxalate (LiODFB) and lithium dioxalatoborate (LiB(C2O4)2, LiBOB).

[0057] The nitrile compound may be at least one compound selected from the group consisting of succinonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, octanonitrile, heptanecarbonitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, benzyl cyanide, 2-fluorophenyl cyanide and 4-fluorophenyl cyanide.

[0058] The benzene-based compound may include fluorobenzene, the amine-based compound may include triethanolamine or ethylenediamine, and the silane-based compound may include tetravinylsilane.

[0059] Lithium salt compounds are different from lithium salts contained in non-aqueous electrolytes and may include lithium difluorophosphate (LiDFP), LiPO2F2 or LiBF4. Among them, LiPO2F2 can play a role in reducing the increased resistance. Specifically, LiPO2F2 will be reduced during the initial activation process, thereby forming an inorganic film containing F and P on the electrode, and such an inorganic film can improve the durability of the SEI layer and inhibit further reaction of the electrolyte. Therefore, the increase in resistance caused by electrolyte decomposition is suppressed, so that the resistance of the cylindrical lithium secondary battery can be reduced.

[0060] Based on the total weight of the electrolyte, the content of LiPO2F2 in the electrolyte may be 0.01 wt% to 1 wt%, preferably 0.1 wt% to 1 wt%, and more preferably 0.2 wt% to 0.8 wt%. When the content of LiPO2F2 satisfies the above range, an inorganic film containing an appropriate amount of F and P may be formed on the electrode during the initial activation process. Therefore, the durability of the SEI layer may be excellent, the initial resistance may be sufficiently reduced, and the high temperature storage performance may also be very excellent.

[0061] When a combination of vinylene carbonate (VC), 1,3-propane sultone (PS) and lithium difluorophosphate (LiPO2F2) among these other electrolyte additives is additionally added, a more stable SEI film can be formed on the negative electrode surface during the initial activation process of the secondary battery, and gas generation due to decomposition of the electrolyte at high temperature can be suppressed, thereby improving the high temperature stability of the secondary battery.

[0062] The electrolyte may also include a compound selected from the group consisting of succinonitrile, propargyl-1H-imidazole-1-carboxylate and methyl prop-2-ynyl carbonate. Based on the total weight of the electrolyte, the content of succinonitrile in the electrolyte may be 0.01 wt % to 0.5 wt %. Based on the total weight of the electrolyte, the content of propargyl-1H-imidazole-1-carboxylate in the electrolyte may be 0.01 wt % to 1 wt %. Based on the total weight of the electrolyte, the content of methyl prop-2-ynyl carbonate in the electrolyte may be 0.01 wt % to 1 wt %.

[0063] Electrode assembly

[0064] The electrode assembly is a jelly-roll type electrode assembly having a structure in which a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate are wound in one direction.

[0065] The electrode assembly of the present invention may be manufactured by winding a laminate formed by stacking a separator, a positive electrode plate, a separator, and a negative electrode plate in sequence at least once in one direction.

[0066] In this case, the positive electrode plate and the negative electrode plate may have a structure in which an active material layer is formed on a long sheet-like current collector, and may include an uncoated portion in which the active material layer is not formed on a partial region of the current collector.

[0067] When the positive and negative electrode plates including the uncoated portions are used, a battery without a tab structure without separate electrode tabs can be realized, and at least a portion of the uncoated portions of the positive and negative electrode plates defines the electrode tabs.

[0068] Specifically, the uncoated portion can be formed at one end of the collector and extend along the winding direction. By joining the collector plate to the uncoated portion of the positive electrode plate and the uncoated portion of the negative electrode plate, and connecting the collector plate to the electrode terminal, a battery with a tab-free structure can be realized.

[0069] For example, a battery with a tab-free structure can be manufactured by the following method. First, a separator, a positive plate, a separator, and a negative plate are stacked in sequence so that the uncoated portions of the positive plate and the negative plate are located in opposite directions, and then wound in one direction to manufacture a jelly roll type electrode assembly. Then, the uncoated portions of the positive plate and the negative plate are bent in the direction of the winding center; the collector plate is welded and joined to the uncoated portions of the positive plate and the negative plate respectively; and then the collector plate is connected to the electrode terminal to manufacture a battery with a tab-free structure. At the same time, compared with the strip electrode tab, the collector plate has a larger cross-sectional area, and the resistance is inversely proportional to the cross-sectional area of ​​the current flow path. Therefore, when the secondary battery adopts the above structure, the battery resistance can be greatly reduced.

[0070] The uncoated portions of the positive electrode plate and the negative electrode plate may be processed into the form of a plurality of independently bendable segmented pieces, and at least a portion of the plurality of segmented pieces may be bent toward a winding center of the electrode assembly.

[0071] The current collectors of the positive and negative plates may be processed by a metal foil cutting process (eg, laser slotting, ultrasonic cutting, and stamping) to form segmented pieces.

[0072] When the uncoated portions of the positive and negative electrode plates are processed in the form of multiple segmented pieces, stress applied to the uncoated portions during bending is reduced, thereby preventing deformation or damage of the uncoated portions and improving welding characteristics with the collector plates.

[0073] The collector plate and the uncoated portion are generally joined by welding. In order to improve the welding characteristics, the uncoated portion must be bent as flat as possible by applying strong pressure to the welding area of ​​the uncoated portion. However, during this bending process, the shape of the uncoated portion may be deformed due to irregular twisting, and the deformed portion may contact the electrode of the opposite polarity to cause an internal short circuit or cause fine cracks in the uncoated portion. However, if the uncoated portions of the positive and negative plates are processed into the form of multiple independently bendable segmented pieces, the stress applied to the uncoated portion during the bending process can be reduced, thereby minimizing the deformation and damage of the uncoated portion.

[0074] In addition, when the uncoated portion is processed in the form of the above-mentioned segmented pieces, the multiple segmented pieces overlap during the bending process, thereby increasing the welding strength with the collector plate, and when the latest technology such as laser welding is used, it is possible to prevent the laser from penetrating into the electrode assembly to ablate the diaphragm or active material. Preferably, at least a portion of the multiple curved segmented pieces can be overlapped on the upper end and the lower end of the electrode assembly, and the collector plate can be joined to the multiple curved segmented pieces.

[0075] Next, the respective components of the electrode assembly of the present invention will be described in more detail.

[0076] (1) Positive plate

[0077] The positive electrode plate may have a structure in which a positive electrode active material layer is formed on one or both surfaces of a long sheet-shaped positive electrode collector, wherein the positive electrode active material layer may include a positive electrode active material, a conductive material, and a binder.

[0078] Specifically, the positive electrode plate can be prepared by applying a positive electrode slurry to one or both surfaces of a long sheet of positive electrode collector, removing the solvent of the positive electrode slurry through a drying process, and then rolling it, wherein the positive electrode slurry is prepared by dispersing a positive electrode active material, a conductive material, and a binder in a solvent such as dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone, water, etc. At the same time, a positive electrode plate including an uncoated portion can be prepared by not applying the positive electrode slurry to a partial area of ​​the positive electrode collector (for example, one end of the positive electrode collector) when applying the positive electrode slurry.

[0079] As the positive electrode collector, various positive electrode collectors used in the art can be used. For example, the positive electrode collector can be stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel whose surface is treated with carbon, nickel, titanium, silver, etc. The positive electrode collector can generally have a thickness of 3 to 500 μm, and fine concavoconvexities can be formed on the surface of the positive electrode collector to improve the adhesion of the positive electrode active material. For example, the positive electrode collector can be used in various forms, such as a film, a sheet, a foil, a net, a porous body, a foam or a non-woven fabric, etc.

[0080] Meanwhile, as the positive electrode active material, any positive electrode active material generally used in the art may be used.

[0081] Preferably, the positive electrode active material may include a lithium nickel oxide, specifically, a lithium nickel oxide containing 80 mol% or more of Ni based on the total molar number of the transition metal. Preferably, the content of Ni in the lithium nickel oxide may be 80 mol% or more and less than 100 mol%, or 82 mol% or more and less than 100 mol%, or 83 mol% or more and less than 100 mol%. When a lithium nickel oxide with a high Ni content as described above is used, a high capacity can be achieved.

[0082] More specifically, the positive electrode active material may include a lithium nickel-based oxide represented by the following Chemical Formula 1:

[0083] [Chemical formula 1]

[0084] Li a Ni b Co c M 1 d M 2 e O2

[0085] In Chemical Formula 1, M 1 may be Mn, Al, or a combination thereof, preferably Mn or Mn and Al.

[0086] M 2 may be at least one selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta, and Nb, preferably at least one selected from the group consisting of Zr, Y, Mg, and Ti, more preferably Zr, Y, or a combination thereof. Element M is not necessarily included 2 , but when included in an appropriate amount, it can play a role in promoting grain growth during firing or improving the crystal structure stability.

[0087] a represents the molar ratio of lithium in the lithium nickel-based oxide, and can be 0.8 ≤ a ≤ 1.2, 0.85 ≤ a ≤ 1.15, or 0.9 ≤ a ≤ 1.2. When the molar ratio of lithium satisfies the above range, the crystal structure of the lithium nickel-based oxide can be stably formed.

[0088] b represents the molar ratio of nickel in all metals other than lithium in the lithium nickel-based oxide, and can be 0.8 ≤ b < 1, 0.85 ≤ b < 1, 0.86 ≤ b < 1, or 0.88 ≤ b < 1. When the molar ratio of nickel satisfies the above range, a high energy density can be exhibited, thereby achieving a high capacity.

[0089] c represents the molar ratio of cobalt in all metals other than lithium in the lithium nickel-based oxide, and can be 0 < c < 0.2, 0 < c < 0.15, 0 < c < 0.14, or 0.01 ≤ c ≤ 0.12. When the molar ratio of cobalt satisfies the above range, good resistance characteristics and output characteristics can be achieved.

[0090] d represents the molar ratio of element M in all metals other than lithium in the lithium nickel-based oxide 1 and can be 0 < d < 0.2, 0 < d < 0.15, 0 < d < 0.14, or 0.01 ≤ d ≤ 0.12. When the molar ratio of element M 1 satisfies the above range, the structural stability of the positive electrode active material is excellent.

[0091] e represents the molar ratio of element M in all metals other than lithium in the lithium nickel-based oxide 2 and can be 0 ≤ e ≤ 0.1, or 0 ≤ e ≤ 0.05.

[0092] Meanwhile, if necessary, the positive electrode active material of the present invention may further include a coating layer containing one or more coating elements selected from the group consisting of Al, Ti, W, B, F, P, Mg, Ni, Co, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si and S on the surface of the lithium nickel oxide particles. Preferably, the coating element may be Al, B, Co or a combination thereof, and most preferably B.

[0093] When there is a coating layer on the surface of the lithium nickel-based oxide particles, the coating layer can inhibit contact between the electrolyte and the lithium composite transition metal oxide, thereby having the effect of reducing transition metal dissolution or gas generation due to side reactions with the electrolyte.

[0094] The content of the positive electrode active material may be 80 to 99 wt %, preferably 85 to 99 wt %, and more preferably 90 to 99 wt %, based on the total weight of the positive electrode active material layer.

[0095] Meanwhile, the positive electrode active material is not particularly limited in its form, and may be in the form of secondary particles in which a plurality of primary particles are aggregated, in the form of a single particle formed of one primary particle, or in the form of a combination thereof.

[0096] Preferably, the positive electrode active material may include a single particle formed of one primary particle and / or a quasi-single particle as an aggregate of 10 or less primary particles. By using a single particle formed of one primary particle and / or a quasi-single particle as an aggregate of 10 or less primary particles as a positive electrode active material, a large cylindrical battery having excellent safety while achieving high capacity can be obtained.

[0097] In the past, as a positive electrode active material for lithium secondary batteries, spherical secondary particles formed by the aggregation of tens to hundreds of primary particles are generally used. However, in the case of a positive electrode active material in the form of secondary particles formed by the aggregation of a large number of primary particles, there is a problem of particle rupture in which primary particles are easily detached during the calendering process when manufacturing the positive electrode, and cracking inside the particles during the charge and discharge process. When the particles of the positive electrode active material are ruptured or cracking inside the particles occurs, the contact area with the electrolyte increases, thereby causing the problem of increased gas generation due to side reactions with the electrolyte. If the gas generation inside the cylindrical battery increases, the pressure inside the battery increases, resulting in the risk of battery explosion. In particular, when the volume of the cylindrical battery increases, the amount of active material inside the battery increases as the volume increases, so the amount of gas generated increases significantly, thereby increasing the risk of battery fire and / or explosion.

[0098] In contrast, in the case of a single particle formed by one primary particle or a quasi-single particle formed by the aggregation of less than 10 primary particles, the particle strength is higher than that of a conventional secondary particle-type positive electrode active material formed by the aggregation of tens to hundreds of primary particles, so it is difficult for particles to break during the rolling process. In addition, in the case of a single particle or quasi-single particle positive electrode active material, the number of primary particles constituting the particle is small, so that the change caused by the volume expansion and contraction of the primary particles during the charge and discharge process is small, so the occurrence of cracking inside the particle is also significantly reduced.

[0099] Therefore, when a cathode active material formed of a single particle or a quasi-single particle is used, the amount of gas generated due to particle fracture or internal cracking can be significantly reduced, thereby achieving excellent safety even in a large cylindrical battery.

[0100] At the same time, based on the weight of the total positive electrode active material contained in the positive electrode active material layer, the content of the positive electrode active material formed by the single particle and / or the quasi-single particle is preferably 95 wt % to 100 wt %, preferably 98 wt % to 100 wt %, more preferably 99 wt % to 100 wt %, and even more preferably 100 wt %. When the content of the single particle and / or the quasi-single particle satisfies the above range, sufficient safety can be obtained when applied to large cylindrical batteries.

[0101] Meanwhile, the average particle size D of the positive electrode active material in the form of single particles and / or quasi-single particles of the present invention is 50 It may be 5 μm or less, 4 μm or less, 3 μm or less, or 2 μm or less, for example, 0.5 μm to 5 μm, preferably 1 μm to 5 μm, and more preferably 2 μm to 5 μm. 50 When the above range is satisfied, the increase in resistance can be minimized.

[0102] Since the interface between primary particles, which is the diffusion path of lithium ions inside the particles, is smaller in the single particle and / or quasi-single particle form of the positive electrode active material, the lithium mobility is lower than that of the secondary particle form of the positive electrode active material, thereby increasing the resistance. As the particle size increases, the increase in resistance becomes more serious, and the increased resistance has a negative impact on the capacity and output characteristics. Therefore, in the present invention, a small average particle size D of 5 μm or less is used. 50 The cathode active material is in the form of a single particle or quasi-single particle to minimize the diffusion distance of lithium ions within the particle, thereby suppressing the increase in resistance.

[0103] The average primary particle size of the positive electrode active material in the form of a single particle and / or a quasi-single particle may be less than 5 μm, less than 4 μm, less than 3 μm or less than 2 μm, for example, 0.5 μm to 5 μm, preferably 1 μm to 5 μm, and more preferably 2 μm to 5 μm. When the average primary particle size meets the above range, a single particle and / or a quasi-single particle positive electrode active material with excellent electrochemical properties can be formed. If the average particle size of the primary particles is too small, the number of aggregated primary particles forming the positive electrode active material will increase, reducing the effect of suppressing particle breakage during the rolling process. If the average particle size of the primary particles is too large, the lithium diffusion path inside the primary particles will become longer, which may lead to an increase in resistance and a decrease in output characteristics.

[0104] In the present invention, the positive electrode active material in the form of a single particle and / or a quasi-single particle preferably has a unimodal particle size distribution. Traditionally, in order to improve the electrode density of the positive electrode active material layer, a bimodal positive electrode active material using a mixture of a large-particle positive electrode active material having a larger average particle size and a small-particle positive electrode active material having a smaller average particle size is widely used. However, in the case of a positive electrode active material in the form of a single particle or a quasi-single particle, as the particle size increases, the movement path of lithium becomes longer, thereby significantly increasing the resistance. Therefore, when large-particle particles are used in combination, the capacity and output characteristics may deteriorate. Therefore, in the present invention, by using a unimodal distribution of positive electrode active materials, the increase in resistance can be minimized.

[0105] Next, the conductive material is used to impart conductivity to the electrode, and can be any material without particular limitation, as long as it has conductivity and does not cause chemical changes in the constructed battery. Specific examples thereof may include: graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber and carbon nanotubes; metal powders or fibers, such as copper, nickel, aluminum, silver, etc.; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, any one of which or a mixture of two or more thereof can be used. Based on the total weight of the positive electrode active material layer, the content of the conductive material can generally be 1 to 30% by weight, preferably 1 to 20% by weight, and more preferably 1 to 10% by weight.

[0106] Binder is used to improve the bonding between the positive active material particles and the adhesion between the positive active material and the positive collector. Its specific examples may include: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM rubber), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or their various copolymers, any one or a mixture of two or more thereof can be used. Based on the total weight of the positive active material layer, the content of the binder can generally be 1 to 30% by weight, preferably 1 to 20% by weight, and more preferably 1 to 10% by weight.

[0107] Meanwhile, if necessary, an insulating layer covering a portion of the positive electrode active material layer and a portion of the uncoated portion may be further formed on the positive electrode plate of the present invention. The insulating layer may be formed in a direction parallel to the winding direction of the electrode assembly.

[0108] The voids in the positive electrode plate are preferably 22 volume % to 24 volume %, preferably 23 volume % to 24 volume %, based on the total volume of the positive electrode plate.

[0109] (2) Negative plate

[0110] The negative electrode plate may have a structure in which a negative electrode active material layer is formed on one or both surfaces of a long sheet-shaped negative electrode collector, wherein the negative electrode active material layer may include a negative electrode active material, a conductive material, and a binder.

[0111] Specifically, the negative electrode plate can be prepared by applying the negative electrode slurry to one or both surfaces of the long sheet-shaped negative electrode collector, removing the solvent of the negative electrode slurry through a drying process, and then rolling it, wherein the negative electrode slurry is prepared by dispersing the negative electrode active material, the conductive material and the binder in a solvent such as dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), acetone, water, etc. At the same time, the negative electrode plate including the uncoated portion can be prepared by not applying the negative electrode slurry to a partial area of ​​the negative electrode collector (for example, one end of the negative electrode collector) when applying the negative electrode slurry.

[0112] As the negative electrode active material, a compound that can reversibly intercalate and deintercalate lithium can be used. Specific examples of negative electrode active materials may include: carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, amorphous carbon; Si, Si-Me alloy (where Me is at least one selected from the group consisting of Al, Sn, Mg, Cu, Fe, Pb, Zn, Mn, Cr, Ti and Ni), SiO y(where 0 < y < 2) and silicon-based materials such as Si-C composite materials; lithium metal thin films; metal materials such as Sn and Al that can alloy with lithium; any one or a mixture of two or more thereof can be used.

[0113] Preferably, the negative electrode plate of the present invention may include a silicon-based negative electrode active material. The silicon-based negative electrode active material may be Si, Si-Me alloy (where Me is at least one selected from the group consisting of Al, Sn, Mg, Cu, Fe, Pb, Zn, Mn, Cr, Ti, and Ni), SiO y (0 < y < 2), Si-C composite material, or a combination thereof, preferably may be SiO y (0 < y < 2). Since the silicon-based negative electrode active material has a high theoretical capacity, the capacity characteristics can be improved when the silicon-based negative electrode active material is included.

[0114] Meanwhile, the silicon-based negative electrode active material may be doped with M b metal, wherein the M b metal may be a Group 1 metal element or a Group 2 metal element, specifically Li, Mg, etc. Specifically, the silicon negative electrode active material may be Si, SiO b doped with M y (where 0 < y < 2), Si-C composite material, etc. In the case of the metal-doped silicon-based negative electrode active material, due to the doped elements, the capacity of the active material decreases, but it has high efficiency, so high energy density can be achieved.

[0115] In addition, the silicon-based negative electrode active material may further include a carbon coating on the particle surface. At this time, based on the total weight of the silicon-based negative electrode active material, the carbon coating amount may be 20 wt% or less, preferably 1 to 20 wt%.

[0116] In addition, if necessary, the negative electrode plate may further include a carbon-based negative electrode active material as the negative electrode active material. The carbon-based negative electrode active material may be, for example, artificial graphite, natural graphite, graphitized carbon fiber, amorphous carbon, soft carbon, hard carbon, etc., but is not limited thereto.

[0117] Meanwhile, when a mixture of a silicon-based negative electrode active material and a carbon-based negative electrode active material is used as the negative electrode active material, the mixing ratio of the silicon-based negative electrode active material and the carbon-based negative electrode active material may be 1:99 to 20:80, preferably 1:99 to 15:85, more preferably 1:99 to 10:90.

[0118] Based on the total weight of the negative electrode active material layer, the content of the negative electrode active material may be 80 to 99 wt%, preferably 85 to 99 wt%, more preferably 90 to 99 wt%.

[0119] Meanwhile, the negative electrode collector can be any negative electrode collector commonly used in the art, for example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel surface-treated with carbon, nickel, titanium or silver, or aluminum-cadmium alloy, etc. The thickness of the negative electrode collector can generally be 3 to 500 μm, and like the positive electrode collector, fine concave-convex can be formed on the surface of the collector to improve the adhesion of the negative electrode active material. For example, it can be used in various forms, such as a film, a sheet, a foil, a net, a porous body, a foam or a non-woven fabric, etc.

[0120] The conductive material is used to impart conductivity to the negative electrode, and can be any material without particular limitation, as long as it has conductivity and does not cause chemical changes in the constructed battery. Specific examples thereof may include: graphite, such as natural graphite or artificial graphite; carbon materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber and carbon nanotubes; metal powders or fibers, such as copper, nickel, aluminum, silver, etc.; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or conductive polymers, such as polyphenylene derivatives, any one of which or a mixture of two or more thereof can be used. Based on the total weight of the negative electrode active material layer, the content of the conductive material can generally be 1 to 30% by weight, preferably 1 to 20% by weight, and more preferably 1 to 10% by weight.

[0121] The binder is used to improve the bonding between the negative electrode active material particles and the adhesion between the negative electrode active material and the negative electrode collector. Specific examples thereof may include: polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene rubber (EPDM rubber), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber or various copolymers thereof, any one of which or a mixture of two or more thereof may be used. Based on the total weight of the negative electrode active material layer, the content of the binder may generally be 1 to 30% by weight, preferably 1 to 20% by weight, and more preferably 1 to 10% by weight.

[0122] The voids in the negative electrode plate are preferably 22 to 24 volume %, preferably 23 to 24 volume %, based on the total volume of the negative electrode plate.

[0123] (3) Diaphragm

[0124] The separator is used to separate the negative electrode from the positive electrode and provide a channel for lithium ions to move, and any separator can be used without particular limitation, as long as it is commonly used as a separator in a lithium secondary battery. Specifically, as a separator, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin polymer (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer), or a laminated structure of more than two layers can be used. In addition, conventional porous nonwoven fabrics can also be used, such as nonwoven fabrics made of high melting point glass fiber or polyethylene terephthalate fiber, etc. Moreover, in order to ensure heat resistance or mechanical strength, a coated separator comprising a ceramic component or a polymer material can also be used.

[0125] The voids of the separator are preferably 46% to 47% by volume, preferably 47% to 48% by volume, based on the total volume of the separator.

[0126] Cylindrical lithium secondary battery

[0127] Next, a cylindrical lithium secondary battery of the present invention will be described.

[0128] The cylindrical lithium secondary battery of the present invention may be a large-capacity cylindrical secondary battery having a capacity of 25 Ah or more.

[0129] The cylindrical lithium secondary battery of the present invention may be a large cylindrical battery having a shape factor ratio (defined as the diameter of the cylindrical battery divided by its height, i.e., the ratio of the diameter (φ) to the height (H)) of 0.4 or more. Here, the shape factor refers to a value representing the diameter and height of the cylindrical battery.

[0130] The cylindrical battery of the present invention can be, for example, a 46110 battery cell (diameter 46mm, height 110mm, shape factor ratio of 0.418), a 4875 battery cell (diameter 48mm, height 75mm, shape factor ratio of 0.640), a 48110 battery cell (diameter 48mm, height 110mm, shape factor ratio of 0.436), a 4880 battery cell (diameter 48mm, height 80mm, shape factor ratio of 0.600), a 4680 battery cell (diameter 46mm, height 80mm, shape factor ratio of 0.575), and a 4695 battery cell (diameter 46mm, height 95mm, shape factor ratio of 0.484). In the numerical value representing the shape factor, the first two digits represent the diameter of the battery cell, and the next two or three digits represent the height of the battery cell.

[0131] The cylindrical lithium secondary battery of the present invention can significantly reduce the amount of gas generated compared to the prior art, and thus can achieve excellent safety even in a large cylindrical battery with an aspect ratio of 0.4 or more.

[0132] Meanwhile, the cylindrical battery of the present invention is a battery without an electrode tab structure and does not include an electrode tab.

[0133] For example, a battery without a tab structure may have a structure in which the positive electrode plate and the negative electrode plate each include an uncoated portion where an active material layer is not formed, the uncoated portions of the positive electrode and the negative electrode are respectively located at the upper and lower portions of the electrode assembly, the collector plate is joined to the uncoated portion of the positive electrode plate and the uncoated portion of the negative electrode plate, and the collector plate is connected to the electrode terminal.

[0134] Figure 1 A cross-sectional view of a cylindrical battery having a tab-free structure according to an embodiment of the present invention is shown. Figure 1 The cylindrical battery of the embodiment of the present invention is described. However, Figure 1 Only one embodiment of the present invention is shown, and the structure of the cylindrical battery of the present invention is not limited to Figure 1 The scope disclosed in.

[0135] The cylindrical battery 140 according to one embodiment of the present invention includes the above-described jelly-roll type electrode assembly 141 , a battery can 142 accommodating the electrode assembly 141 , and a sealing body 143 sealing an open end of the battery can 142 .

[0136] In this case, the positive electrode plate and the negative electrode plate of the electrode assembly may each include an uncoated portion where no active material layer is formed, and may be stacked and wound so that the uncoated portion of the positive electrode and the uncoated portion of the negative electrode are located at the upper and lower portions of the electrode assembly, respectively. Since the electrode assembly has been described above, only the remaining components other than the electrode assembly will be described below.

[0137] The battery can 142 is a cylindrical container with an opening formed at the top, and is made of a conductive metal material such as aluminum or steel. The battery can accommodate the electrode assembly 141 in the inner space through the top opening, and can also accommodate an electrolyte (not shown).

[0138] Battery Can

[0139] The battery can 142 is electrically connected to the uncoated portion 146 b of the negative electrode plate, serving as a negative electrode terminal that contacts an external power source to transmit current applied from the external power source to the negative electrode plate.

[0140] If necessary, a curling portion 147 and a crimping portion 148 may be provided at the top of the battery can 142. The curling portion 147 may be formed by pressing the circumference of the outer peripheral surface of the battery can 142 into the distance D1. The curling portion 147 prevents the electrode assembly 141 housed in the battery can 142 from escaping through the top opening of the battery can 142, and may be used as a support for mounting the sealing body 143.

[0141] The crimping portion 148 may be formed at an upper portion of the beading portion 147 and have an extended and curved shape to surround an outer circumferential surface of the cap plate 143 a disposed on the beading portion 147 and a portion of an upper surface of the cap plate 143 a .

[0142] Next, the sealing body 143 is used to seal the open end of the battery can 142, and may include a cover plate 143a, a first gasket 143b that provides airtightness and insulation between the cover plate 143a and the battery can 142, and, if necessary, a connecting plate 143c that is electrically and mechanically connected to the cover plate 143a. The cover plate 143a may be crimped onto a crimping portion 147 formed in the battery can 142 and fixed by a crimping portion 148.

[0143] The cap plate 143a is a component made of a conductive metal material, covering the top opening of the battery can 142. The cap plate 143a is electrically connected to the positive plate of the electrode assembly 141 and is electrically insulated from the battery can 142 by the first gasket 143b. Therefore, the cap plate 143a can be used as a positive terminal of a cylindrical secondary battery. The cap plate 143a may include a protrusion 143d formed to protrude upward from its center (C), wherein the protrusion 143d may be in contact with an external power source to allow current to be applied from the external power source.

[0144] The first gasket 143 b may be inserted between the cap plate 143 a and the crimping portion 148 to ensure airtightness of the battery can 142 and electrical insulation between the battery can 142 and the cap plate 143 a .

[0145] Meanwhile, the cylindrical battery 140 of the present invention may further include collector plates 144 and 145 as necessary. The collector plates are joined to the uncoated portions 146a and 146b of the positive and negative plates and connected to electrode terminals (ie, positive and negative terminals).

[0146] Specifically, the cylindrical battery 140 of the present invention may include a first collector plate 144 coupled to an upper portion of the electrode assembly 141 and a second collector plate 145 coupled to a lower portion of the electrode assembly 141 .

[0147] It may further include a first collector plate 144 and / or a second collector plate 145 .

[0148] The first collector plate 144 is joined to the upper portion of the electrode assembly 141. The first collector plate 144 is made of a conductive metal material such as aluminum, copper, nickel, etc., and is electrically connected to the uncoated portion 146a of the positive electrode plate. A lead 149 may be connected to the first collector plate 144. The lead 149 may extend upward from the electrode assembly 141 and be joined to the connecting plate 143c, or may be directly joined to the lower surface of the cover plate 143a. The lead 149 and other components may be joined by welding. Preferably, the first collector plate 144 may be formed integrally with the lead 149. In this case, the lead 149 may have a long plate shape extending outward from the center of the first collector plate 144.

[0149] At the same time, the first collector plate 144 is joined to the end of the non-coated portion 146 a of the positive electrode plate, and the joining may be performed by, for example, laser welding, resistance welding, ultrasonic welding, brazing, or the like.

[0150] The second collector plate 145 is joined to the lower portion of the electrode assembly 141. The second collector plate 145 is made of a conductive metal material such as aluminum, copper, nickel, etc., and is electrically connected to the uncoated portion 146b of the negative electrode plate. One surface of the second collector plate 145 may be joined to the uncoated portion 146b of the negative electrode plate, and the opposite surface may be joined to the inner lower surface of the battery can 142. In this case, the joining may be performed by laser welding, resistance welding, ultrasonic welding, or brazing.

[0151] Meanwhile, the cylindrical battery 140 of the present invention may further include an insulator 146 if necessary. The insulator 146 may be provided to cover the upper surface of the first collector plate 144. By covering the first collector plate 144 with the insulator 146, the first collector plate 144 may be prevented from directly contacting the inner circumferential surface of the battery can 142.

[0152] The insulator 146 has a lead hole 151 through which the lead 149 extending upward from the first collector plate 144 can be led out. The lead 149 is led out upward through the lead hole 151 and is bonded to the lower surface of the connection plate 143c or the lower surface of the cap plate 143a.

[0153] The insulator 146 may be made of an insulating polymer resin such as polyethylene, polypropylene, polyimide, or polybutylene terephthalate.

[0154] Meanwhile, the cylindrical battery 140 of the present invention may further include a vent 152 formed on the lower surface of the battery can 142 when necessary. The vent 152 corresponds to an area of ​​the lower surface of the battery can 142 that is thinner than the surrounding area. Since the vent 152 is thinner, it is structurally weaker than the surrounding area. Therefore, when the pressure inside the cylindrical battery 140 rises above a certain level, the vent 152 ruptures and the gas inside the battery can 142 is discharged to the outside, thereby preventing the battery from exploding.

[0155] Figure 2 A cross-sectional view of a cylindrical battery having a tab-free structure according to another embodiment of the present invention is shown. Figure 2 A cylindrical battery according to another embodiment of the present invention is described. However, Figure 2 Only one embodiment of the present invention is shown, and the structure of the cylindrical battery of the present invention is not limited to Figure 2 The scope disclosed in.

[0156] Reference Figure 2 ,and Figure 1 Compared with the cylindrical battery 140 shown in FIG. 1 , the cylindrical battery 170 according to another embodiment of the present invention has different structures of a battery can and a sealing body, but the configurations of an electrode assembly and an electrolyte are substantially the same.

[0157] Specifically, the cylindrical battery 170 includes a battery can 171, and a rivet terminal 172 is inserted through and installed in the battery can 171. The rivet terminal 172 is installed on a partially closed surface (upper surface in the figure) at one end of the battery can 171. The rivet terminal 172 is riveted to the through hole (first opening at the first end) of the battery can 171 in a state where an insulating second gasket 173 is inserted. The rivet terminal 172 is exposed outward in a direction opposite to the direction of gravity.

[0158] The rivet terminal 172 includes a terminal exposure portion 172a and a terminal insertion portion 172b. The terminal exposure portion 172a is exposed outside the closed surface of the battery can 171. The terminal exposure portion 172a may be approximately located at the center of the partially closed surface of the battery can 171. The maximum diameter of the terminal exposure portion 172a may be formed to be larger than the maximum diameter of the through hole formed in the battery can 171. The terminal insertion portion 172b may approximately penetrate the center of the closed surface of the battery can 171 and be electrically connected to the uncoated portion 146a of the positive plate. The terminal insertion portion 172b may be riveted to the inner surface of the battery can 171. That is, the end of the terminal insertion portion 172b may have a shape bent toward the inner surface of the battery can 171. The maximum diameter of the end of the terminal insertion portion 172b may be larger than the maximum diameter of the through hole of the battery can 171.

[0159] The lower surface of the terminal insertion portion 172b can be welded to the first collector plate 144 connected to the uncoated portion 146a of the positive plate. The insulating cover 174 made of an insulating material can be inserted between the first collector plate 144 and the inner surface of the battery can 171. The insulating cover 174 covers the upper portion of the first collector plate 144 and the upper end edge portion of the electrode assembly 141. Therefore, the peripheral uncoated portion B3 of the electrode assembly 141 can be prevented from contacting the inner surface of the battery can 171 with different polarities, thereby causing a short circuit. The terminal insertion portion 172b of the rivet terminal 172 can pass through the insulating cover 174 and be welded to the first collector plate 144.

[0160] The second gasket 173 is inserted between the battery can 171 and the rivet terminal 172 to prevent the battery can 171 and the rivet terminal 172 having opposite polarities from electrically contacting each other. Thus, the upper surface of the battery can 171 having a substantially flat shape can be used as a positive terminal of the cylindrical battery 170.

[0161] The second gasket 173 includes a gasket exposed portion 173a and a gasket inserted portion 173b. The gasket exposed portion 173a is inserted between the terminal exposed portion 172a of the rivet terminal 172 and the battery can 171. The gasket inserted portion 173b is inserted between the terminal inserted portion 172b of the rivet terminal 172 and the battery can 171. The gasket inserted portion 173b can be deformed together when the terminal inserted portion 172b is riveted and can be in close contact with the inner surface of the battery can 171. The second gasket 173 can be made of, for example, a polymer resin having insulating properties.

[0162] The gasket exposed portion 173a of the second gasket 173 may have a shape extending to cover the outer peripheral surface of the terminal exposed portion 172a of the rivet terminal 172. When the second gasket 173 covers the outer peripheral surface of the rivet terminal 172, it is possible to prevent a short circuit from occurring during the process of joining an electrical connection component such as a bus bar to the upper surface of the battery can 171 and / or the rivet terminal 172. Although not shown in the drawings, the gasket exposed portion 173a may have a shape extending to cover not only the outer peripheral surface of the terminal exposed portion 172a but also a portion of its upper surface.

[0163] When the second gasket 173 is made of a polymer resin, the second gasket 173 may be joined to the battery can 171 and the rivet terminal 172 by thermal fusion. In this case, it is possible to strengthen the airtightness at the joining interface between the second gasket 173 and the rivet terminal 172 and the joining interface between the second gasket 173 and the battery can 171. Meanwhile, when the gasket exposed portion 173a of the second gasket 173 has a shape extending to the upper surface of the terminal exposed portion 172a, the rivet terminal 172 may be integrally joined to the second gasket 173 by insert injection.

[0164] The remaining area 175 of the upper surface of the battery can 171 excluding the area occupied by the rivet terminal 172 and the second gasket 173 corresponds to a negative terminal having a polarity opposite to that of the rivet terminal 172 .

[0165] The second collector plate 176 is coupled to the lower portion of the electrode assembly 141. The second collector plate 176 is made of a conductive metal material such as aluminum, steel, copper, nickel, etc., and is electrically connected to the uncoated portion 146b of the negative electrode plate.

[0166] The second collector plate 176 is preferably electrically connected to the battery can 171. To this end, at least a portion of the edge portion of the second collector plate 176 may be inserted and fixed between the inner surface of the battery can 171 and the first gasket 178b. In one example, at least a portion of the edge portion of the second collector plate 176 may be fixed to the curling portion 180 by welding, while being supported on the bottom surface of the curling portion 180 formed at the bottom of the battery can 171. In a modified example, at least a portion of the edge portion of the second collector plate 176 may be directly welded to the inner wall surface of the battery can 171.

[0167] The second collector plate 176 may include a plurality of concavo-convex (not shown) radially formed on a surface facing the non-coating portion 146 b. When the concavo-convex is formed, the concavo-convex may be pressed into the non-coating portion 146 b by pressing the second collector plate 176 .

[0168] Preferably, the second current collecting plate 176 and the end of the non-coating portion 146 b may be joined to each other by welding (eg, laser welding).

[0169] The sealing body 178 that seals the lower open end of the battery can 171 includes a cover plate 178a and a first gasket 178b. The first gasket 178b electrically separates the cover plate 178a and the battery can 171. The crimping portion 181 fixes the edge of the cover plate 178a and the first gasket 178b together. The cover plate 178a includes a vent 179. The configuration of the vent 179 is substantially the same as that of the above-mentioned embodiment.

[0170] The cover plate 178a is preferably made of a conductive metal material. However, since the first gasket 178b is inserted between the cover plate 178a and the battery can 171, the cover plate 178a has no electrical polarity. The seal 178 is used to seal the open end of the lower part of the battery can 171 and discharge gas when the internal pressure of the battery cell 170 increases above a threshold value.

[0171] Preferably, the rivet terminal 172 electrically connected to the uncoated portion 146a of the positive electrode plate is used as a positive terminal. In addition, a portion 175 other than the rivet terminal 172 in the upper surface of the battery can 171 electrically connected to the uncoated portion 146b of the negative electrode plate through the second collector plate 176 is used as a negative terminal. As described above, when the two electrode terminals are located at the upper portion of the cylindrical battery, an electrical connection component such as a bus bar may be provided only on one side of the cylindrical battery 170.

[0172] This can simplify the structure of the battery pack and improve energy density. In addition, since the portion 175 used as the negative terminal has a substantially flat shape, it is possible to ensure that there is a sufficient bonding area for bonding electrical connection components such as bus bars. Therefore, the cylindrical battery 170 can reduce the resistance at the bonding point of the electrical connection components to a desired level.

[0173] When a cylindrical lithium secondary battery is formed with the above-mentioned tab-free structure, the current concentration is lower than that of a conventional battery with electrode tabs, so the heat generated inside the battery can be effectively reduced, thereby improving the thermal safety of the battery.

[0174] Hereinafter, the present invention will be described in more detail through specific examples.

[0175] Example

[0176] Example 1

[0177] The non-aqueous solvent was prepared by dissolving LiPF6 in an organic solvent (ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) = 20:5:75 volume ratio) to 1.3 M. Based on the total weight of the electrolyte, 2 wt% of vinylene carbonate (VC), 1 wt% of 1,3-propane sultone (PS), 0.2 wt% of succinonitrile, 0.3 wt% of propargyl-1H-imidazole-1-carboxylate and 0.2 wt% of LiPO2F2 were added to prepare the electrolyte. The viscosity of the prepared electrolyte at 20°C was 4.1 cP.

[0178] The positive electrode active material Li[Ni 0.9 Co 0.06 Mn 0.03 Al 0.01 ]O2, carbon nanotubes and PVDF binder are mixed in N-methylpyrrolidone in a weight ratio of 97.8:0.6:1.6 to prepare a positive electrode slurry, wherein the positive electrode active material has a monomodal particle size distribution, D 50 The particle size was 3 μm and in the form of a single particle. The positive electrode slurry was coated on one surface of an aluminum current collector sheet, dried at 120° C., and then rolled to prepare a positive electrode plate.

[0179] The negative electrode active material (graphite: SiO = 95:5 weight ratio mixture), conductive material (super C), styrene butadiene rubber (SBR) and carboxymethyl cellulose (CMC) were mixed in water at a weight ratio of 96:2:1.5:0.5 to prepare a negative electrode slurry. The negative electrode slurry was coated on one surface of a copper collector sheet, dried at 150°C, and then rolled to make a negative electrode plate.

[0180] A separator is inserted between the positive plate and the negative plate prepared above, and the separator is stacked in the order of separator / positive plate / separator / negative plate, and then wound to prepare a jelly roll type electrode assembly. The electrode assembly prepared above is inserted into a cylindrical battery can. Then, the electrolyte is injected so that the volume occupied by the electrolyte is 101 volume % based on the total pore volume of the positive plate, the negative plate and the separator, thereby manufacturing a 4680 battery cell.

[0181] Example 2

[0182] A 4680 battery cell was manufactured in the same manner as in Example 1, except that the electrolyte was injected so that the volume occupied by the electrolyte was 116 volume % based on the total pore volume of the positive electrode plate, the negative electrode plate, and the separator.

[0183] Example 3

[0184] The non-aqueous solvent was prepared by dissolving LiPF6 in an organic solvent (ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) = 20:5:75 volume ratio) to 1.2 M. Based on the total weight of the electrolyte, 2 wt% of vinylene carbonate (VC), 1 wt% of 1,3-propane sultone (PS), 0.2 wt% of succinonitrile, 0.3 wt% of propargyl-1H-imidazole-1-carboxylate and 0.2 wt% of LiPO2F2 were added to prepare the electrolyte. The viscosity of the prepared electrolyte at 20°C was 3.5 cP.

[0185] A 4680 battery cell was manufactured in the same manner as in Example 1 except that the above electrolyte was injected.

[0186] Comparative Example 1

[0187] A 4680 battery cell was manufactured in the same manner as in Example 1, except that the electrolyte was injected so that the volume occupied by the electrolyte was 100 volume % based on the total pore volume of the positive electrode plate, the negative electrode plate, and the separator.

[0188] Comparative Example 2

[0189] A 4680 battery cell was manufactured in the same manner as in Example 1, except that the electrolyte was injected so that the volume occupied by the electrolyte was 120 volume % based on the total pore volume of the positive electrode plate, the negative electrode plate, and the separator.

[0190] Experimental Example - Evaluation of Low Temperature Life Characteristics

[0191] The low temperature life characteristics of the 4680 cells in Examples 1 to 3 and Comparative Examples 1 and 2 were evaluated.

[0192] Specifically, the 4680 cells of Examples 1 to 3 and Comparative Examples 1 and 2 were each subjected to 150 charge and discharge cycles, wherein one cycle consisted of charging to 4.2V at a constant current of 0.5C and discharging to 2.5V at a constant current of 0.5C at 20°C, and then measuring the capacity retention rate after 150 cycles compared to the initial capacity. The results are shown in Table 1 below.

[0193] [Table 1]

[0194] Capacity retention rate (%) Example 1 91 Example 2 85 Example 3 84 Comparative Example 1 70 Comparative Example 2 50

[0195] As shown in Table 1 above, it can be confirmed that in the lithium secondary battery in which the injection fraction is adjusted as in Examples 1 to 3 so that the volume occupied by the electrolyte is greater than 101 volume % and less than 119 volume % based on the total pore volume of the positive electrode plate, the negative electrode plate and the separator, the low-temperature life characteristics are excellent compared to the lithium secondary batteries of Comparative Examples 1 and 2 in which the injection is performed outside the above range.

Claims

1. A lithium secondary battery comprising: an electrode assembly in which a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate are wound in one direction; a battery can accommodating the electrode assembly; an electrolyte injected into the battery can; and a sealing body sealing an open end of the battery can, in, The positive electrode plate and the negative electrode plate each include an uncoated portion where an active material layer is not formed, and at least a portion of the uncoated portion of the positive electrode plate or the negative electrode plate defines an electrode tab, and Wherein, based on the total pore volume of the positive electrode plate, the negative electrode plate and the separator, the volume occupied by the electrolyte is greater than or equal to 101 volume % and less than or equal to 119 volume %.

2. The lithium secondary battery according to claim 1, wherein The volume occupied by the electrolyte is 101 volume % or more and 115 volume % or less based on the total pore volume of the positive electrode plate, the negative electrode plate, and the separator.

3. The lithium secondary battery according to claim 1, wherein The capacity of the lithium secondary battery is greater than 25 Ah.

4. The lithium secondary battery according to claim 1, wherein The lithium secondary battery is a cylindrical battery having a shape factor ratio of 0.4 or more.

5. The lithium secondary battery according to claim 1, wherein The positive electrode plate comprises a positive electrode active material layer containing a positive electrode active material. The positive electrode active material is a lithium nickel oxide represented by the following chemical formula 1: [Chemical formula 1] Li a Ni b Co c M 1 d M 2 e O2 Among them, M 1 Mn, Al or a combination thereof, M 2 is at least one selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta and Nb, 0.8≤a≤1.2, 0.8≤b<1, 0 <c<0.2,0<d<0.2,0≤e≤0.1。 6. The lithium secondary battery according to claim 1, wherein The negative electrode plate comprises a negative electrode active material layer containing a negative electrode active material. The negative electrode active material contained in the negative electrode active material layer is formed of a mixture of a silicon-based negative electrode active material and a carbon-based negative electrode active material.

7. The lithium secondary battery according to claim 6, wherein: The silicon-based anode active material is SiO y (0 < y < 2), and based on the total weight of the anode active material, the content of SiO y (0 < y < 2) is 1 wt% to 5 wt%.

8. The lithium secondary battery according to claim 1, wherein The electrolyte has a viscosity of 3.5 cP or more and 4.2 cP or less at 20°C.

9. The lithium secondary battery according to claim 1, wherein: The electrolyte contains a lithium salt, and the concentration of the lithium salt is 1.0M to 1.5M.

10. The lithium secondary battery according to claim 1, wherein The electrolyte contains an organic solvent, wherein the organic solvent includes ethylene carbonate (EC) and ethyl methyl carbonate (EMC).

11. The lithium secondary battery according to claim 10, wherein: The organic solvent contains ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:0.25 to 1:1.

15.

12. The lithium secondary battery according to claim 10, wherein: The organic solvent further comprises dimethyl carbonate (DMC).

13. The lithium secondary battery according to claim 10, wherein: The organic solvent includes 25 volume % or less of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) based on the total volume of the organic solvent.

14. The lithium secondary battery according to claim 1, wherein The electrolyte includes 0.1 wt % to 3 wt % of vinylene carbonate based on the total weight of the electrolyte.

15. The lithium secondary battery according to claim 1, wherein The electrolyte includes 0.1 wt % to 2 wt % of 1,3-propane sultone based on the total weight of the electrolyte.

16. The lithium secondary battery according to claim 1, wherein The electrolyte includes 0.01 wt % to 1 wt % of lithium difluorophosphate (LiPO 2 F 2 ) based on the total weight of the electrolyte.

Citation Information

Cited By

  • Electrolyte, secondary battery containing electrolyte, and electronic device

    WO2026193848A1